GA3 application in grapes (Vitis vinifera L.) modulates different sets of genes at cluster emergence, full bloom, and berry stage as revealed by RNA sequence-based transcriptome analysis - Upadhyay, Anuradha; Maske, Smita; Jogaiah, Satisha; Kadoo, Narendra Y.; Gupta, Vidya S. (Functional & Integrative Genomics, 2018)
In grapes (Vitis vinifera L.), exogenous gibberellic acid (GA3) is applied at different stages of bunch development to achieve desirable bunch shape and berry size in seedless grapes used for table purpose. RNA sequence-based transcriptome analysis was used to understand the mechanism of GA3 action at cluster emergence, full bloom, and berry stage in table grape variety Thompson Seedless. At cluster emergence, rachis samples were collected at 6 and 24 h after application of GA3, whereas flower clusters and berry samples were collected at 6, 24, and 48 h after application at full bloom and 3–4 mm berry stages. Seven hundred thirty-three genes were differentially expressed in GA3-treated samples. At rachis and flower cluster stage respectively, 126 and 264 genes were found to be significantly differentially expressed within 6 h of GA3 application. The number of DEG reduced considerably at 24 h. However, at berry stage, major changes occurred even at 24 h and a number of DEGs at 6 and 24 h were 174 and 191, respectively. As compared to upregulated genes, larger numbers of genes were downregulated. Stage-specific response to the GA3 application was observed as evident from the unique set of DEGs at each stage and only a few common genes among three stages. Among the DEGs, 67 were transcription factors. Functional categorization and enrichment analysis revealed that several transcripts involved in sucrose and hexose metabolism, hormone and secondary metabolism, and abiotic and biotic stimuli were enriched in response to application of GA3. A high correlation was recorded for real-time PCR and transcriptome data for selected DEGs, thus indicating the robustness of transcriptome data obtained in this study for understanding the GA3 response at different stages of berry development in grape. Chromosomal localization of DEGs and identification of polymorphic microsatellite markers in selected genes have potential for their use in breeding for varieties with improved bunch architecture.
Keywords: Bunch architecture; GA3 response; Microsatellite markers; RNA seq; Transcription factors; Vitis vinifera

Whole proteome analysis of GA(3) response at panicle stage in Grape (Vitis vinifera) CV. Thompson seedless - Maske, Smita; Upadhyay, Anuradha; Jogaiha, Satisha; Patil, Sucheta S.; Kadoo, Narendra Y.; Gupta, Vidya S. (Journal of Plant Growth Regulation, 2019)
Rachis elongation is a crucial process in producing good quality table grapes. In compact clustered grape variety like Thompson Seedless, treating the flower panicles with a mild dose of GA(3) results in loose clusters. We sprayed GA(3) on Thompson Seedless panicles immediately after emergence, and the samples were collected at 6 h and 24 h after application. Whole proteome analysis revealed significant differential expression of 530 proteins of the total 1288 expressed proteins at two time-points. GO term enrichment analysis revealed enrichment of GO terms related to translation, biosynthetic processes, and photosynthesis in GA(3)-treated samples. As the process of rachis elongation requires enhanced carbon metabolism and accumulation of sugars through the expansion of phloem area, we attribute this to the overexpression of several proteins involved in these processes. Significantly highly expressed proteins also belonged to biological processes like the generation of precursor metabolites, cellular protein metabolic processes, response to abiotic stimulus, and protein metabolic processes. This study might be the first of its kind in deciphering the contribution of a different group of proteins during rachis elongation as an early response to GA(3) application in seedless grapes. These results provide quality information on various physiological and biochemical changes occurring during early stages of rachis elongation.
Keywords: Bunch architecture; Gibberellic acid; Proteome; Rachis elongation; Vitis vinifera